계획된 간호 중재가 미숙아 어머니의 스트레스, 모성 역할 긴장과 역할 수행에 미치는 영향 - 정경화; Joung Kyoun -Hwa (Adong Kanho Hakhoe chi, 1999)
The birth of a premature infant is distressing for its parents. The parents of a premature infant experience stress according to the infant's physical appearance and behavior, the environment of the neonatal intensive care unit (NICU) , and the alteration in the parental role. Especially, a mother of a premature infant feels distressed even after the discharge of the infant : therefore, she has difficulties in maternal role performance. The main purpose of this study is to identify the effects of the planned infant care information program in order to lower the stress level for mothers of premature infants caused by the birth and hospitalization in NICU of premature infants, to reduce the maternal role strain, and to promote the maternal role performance after the infants' discharge. This study employed two methods of research at the same time : quasi -experimental non-equivalent pre and post test to compare : non-equivalent post test to compare. The total number of subjects was 19 who were assigned to the research program : 12 mothers of premature infants at the NICU at the Ch university hospital and 7 at the NICU at the Y general hospital located in Chounju city. The data were collected for 79 days from August 18 to November 5, 1998. The questionnaire method was applied for the data collection, and the measures used in this study were Parental Stressor Scale : NICU(Miles, 1993), the Maternal Role Strain Measures ( Hobbs, 1968 ; Steffensmeier, 1982) , and Self Confidence Scale (Pharis, 1978). Research procedure is as follows : after preliminary examination, the experimental subjects, the mothers of premature infants at the Nl CU at Ch university hospital were provided with slide films and information developed by the researcher based on existing documents and data. It took two 60-minute sessions a week for two weeks, and the mothers' stress level was measured using the same instrument twice one week and two week after the infants' hospitalization. The stress level of the contrast subjects, the mothers at Y general hospital was measured during the same period. The experimental subjects were provided with booklets on matters that require attention after the infants' discharge and on developmental project, and they were educated to play the maternal role in person for 2-3 hours a week : breast-feeding, burping a baby, and changing diapers. One week after the infants' discharge, the maternal role strain and the maternal role performance were examined in two groups of the subjects. The analysis of collected data was done using descriptive statistics including real numbers, percentages, averages, and standard deviations. Mann-Whitney test ; x² test ; Repeated Measures Analysis of Variance ; ANCOVA Spearman's rho correlation coefficients. The results on this study were as follows. (1) The examination of the same quality showed that there were no differences in the general and obstetrical characters between the two groups. However, in terms of the characters of premature infants. just right after their birth, the infants at the contrast group weighed more than those at the experimental group(U=16.5, p=.02), and the former was in mother's womb longer than the latter(U=15.5, p=.02). (2) The stress level of the mothers provided with the plannned nursing intervention program became lower as time passed compared to the others'(F=16.61, p=.00) Even when the influence of weight at birth and the length of gestation was removed among the premature infants' characters, the mothers' stress levels made a statistical difference 2 weeks after the infants' hospitalization depending on treatment (F=8.00, p=.01) (3) The maternal role strain of the mothers provided with the planned nursing intervention program was lower than the others'(U=2.0, p=.00). Even when the influence of weight at birth and the length of gestation was removed among the premature infants' characters, the maternal role strain levels made a statistical difference 2 weeks after t